Toward the Madrid Code: nomenclatural proposals of Ukrainian botanists - Hayova V.P.; Boiko G.V.; Mosyakin S.L. (Ukrainian Botanical Journal, 2024)
The International Code of Nomenclature for algae, fungi, and plants is the document that regulates the nomenclature of taxa belonging to these groups of organisms, and thus it is crucially important for maintaining stability of scientific names applied to them. Stable, universal, and properly regulated nomenclature is a solid basis of biological taxonomy and all fields of science and other human activities depending on knowledge of living and fossil organisms. The Code is governed by the users represented by members of the Nomenclature Section of an International Botanical Congress. The Nomenclature Section has a power to modify the Code by voting and taking actions on formal proposals to amend the Code that are submitted by the users before the Congress. In this article, information is provided on the nomenclatural proposals by Ukrainian botanists (and one mycologist), or with participation of Ukrainian botanists, submitted to the XX International Botanical Congress (XX IBC) held in Madrid in July 2024. In total, nine Ukrainian scientists from Kyiv (M.G. Kholodny Institute of Botany of the National Academy of Sciences of Ukraine) and Lviv (Institute of Ecology of the Carpathians of the National Academy of Sciences of Ukraine, Ivan Franko National University of Lviv) have submitted 29 proposals to amend the Code, or 6.7% of the total number of proposals to amend the Code submitted to the XX IBC. These proposals were either single authored, or co-authored by Ukrainian authors and/or authors from other countries. Some of the accepted (3), accepted as amended (2), and rejected proposals are considered and briefly discussed. The participation and contribution of Ukrainian scientists in the process of amending the International Code of Nomenclature for algae, fungi, and plants are emphasized.